The Effect of Corporate Governance Mechanisms on Financial Performance With Capital Structure as an Intervening Variable - Ajijah, Ratna; Uzliawati, Lia; Lestari, Tri (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2024)
This research aims to determine the effect of corporate governance mechanisms proxied by (managerial ownership, institutional ownership and independent board of commissioners) on financial performance with capital structure as an intervening variable. Financial performance is measured using a profitability ratio, proxied by Return On Assets and capital structure proxied by the Debt to Equity ratio. The research population includes property and real estate companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The sample selection method used was purposive sampling and 32 co mpanies were selected with a total sample of 105 research data. The analysis technique used is multiple linear regression with SPSS version 26 software and path analysis with the help of an online sobel calculator. The results showed that managerial ownership, independent board of commissioners had no significant effect on financial performance, while institutional ownership had a positive effect on financial performance. Managerial ownership and independent board of commissioners have a significant positive effect on capital structure, while institutional ownership has no effect on capital structure. The capital structure does not act as a mediator between corporate governance mechanisms and financial performance